All Lives Matter - K. Eslamzadeh, Milad (2024)
the ANEPC for providing data on Portuguese fire incidents and relevant assistance; the ANEPC experts for reviewing the research progress and verifying the results including Jose Pedro Lopes (ANEPC), Comandante Alexandre Penha (ANEPC), Augusto Leite (ANEPC), and two chief commanders of FDs (who preferred to stay anonymous); and the anonymous reviewers for providing their constructive and valuable suggestions that improved the paper’s quality. Publisher Copyright: © 2024 by the authors.